Hubungan Kemandirian dengan Personal Hygiene pada Anak di Pondok Pesantren Kun Assalam Banjardowo Semarang - Umay Matuz Zahro Salsabilla; Kurnia Wijayanti; Nopi Nur Khasanah (Journal of Health, Medical, and Psychological Studies, 2026)
Personal hygiene refers to individual efforts to maintain cleanliness and health to prevent disease, both physically and psychologically. In the pesantren environment, children are required to be more independent in carrying out daily self-care activities such as bathing, brushing teeth, washing hands, and maintaining cleanliness of clothing and living spaces. Preliminary observations at Pondok Pesantren Kun Assalam revealed that several students were still unable to maintain personal hygiene independently, contributing to health problems such as scabies. This research employed a quantitative approach with a cross-sectional design. The sample consisted of 80 students aged 6–18 years selected through total sampling. Data were collected using an independence questionnaire (15 items) and a personal hygiene questionnaire (33 items). Data analysis included univariate and bivariate analyses using the Spearman Rank correlation test. Results most respondents were in the “very independent” category (31 respondents; 38.8%), followed by “fairly independent” (23 respondents; 28.8%), “independent” (22 respondents; 27.5%), and “less independent” (4 respondents; 5%). Personal hygiene levels showed that 38 respondents (47.5%) were in the “good” category, 38 respondents (47.5%) in the “moderate” category, and 4 respondents (5%) in the “poor” category. The Spearman Rank test produced a p-value of 0.000 and r = 0.783, indicating a strong and significant relationship between independence and personal hygiene. The higher the level of independence, the better the personal hygiene of the students.